1996
DOI: 10.1091/mbc.7.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel complexes on the cell surface between integrins and proteins with 4 transmembrane domains (TM4 proteins).

Abstract: Here we identified several new integrin/TM4 protein complexes on the cell surface. By immunoprecipitation using nonstringent conditions, and by reciprocal immunoprecipitation, we found that alpha 3 beta 1 and alpha 6 beta 1 integrins but not alpha 2 beta 1, alpha 5 beta 1, or alpha 6 beta 4 integrins associated with CD9 and CD81 in alpha 3 beta 1/CD81, alpha 3 beta 1/CD9, alpha 6 beta 1/CD81, and alpha 6 beta 1/CD9 complexes. Also, cross-linking experiments established that alpha 3 beta 1/CD81, alpha 3 beta 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
226
2
5

Year Published

1997
1997
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(247 citation statements)
references
References 49 publications
14
226
2
5
Order By: Relevance
“…We have previously demonstrated that CD9 may be physically associated with the gpIIb/IIIa integrin, and others have reported a similar direct association with a,p, integrins (Rubinstein et al, 1994;Nakamura et al, 1995;Berditchevski et al, 1996;Mannion et al, 1996). The present study shows that CD9 can be part of a larger molecular complex consisting of CD9, gpIIb/IIIa and CD42.…”
Section: Discussionsupporting
confidence: 59%
“…We have previously demonstrated that CD9 may be physically associated with the gpIIb/IIIa integrin, and others have reported a similar direct association with a,p, integrins (Rubinstein et al, 1994;Nakamura et al, 1995;Berditchevski et al, 1996;Mannion et al, 1996). The present study shows that CD9 can be part of a larger molecular complex consisting of CD9, gpIIb/IIIa and CD42.…”
Section: Discussionsupporting
confidence: 59%
“…The biological function of the TM-4 family proteins is largely unknown, but recently complexes of TM-4 family proteins with each other and cell surface integrins (Mannion et al, 1996;Berditchevski et al, 1996;Rubinstein et al, 1996) and phosphatidylinositol 4-kinase (Berditchevski et al, 1997) were described, thereby implicating a possible role in cell adhesion and cell signalling for members of this multigen family.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2(A), there were no gross differences in the levels of protein found in the α $ immunoprecipitates from different time points ; moreover, there were no significant differences in the amounts of cell-surface proteins that were isolated in α $ immune complexes ( Figure 2B). It has been reported by others that members of the TM4 (tetraspan 4) family of cell-surface proteins can interact with some integrin α subunits, and that such interactions can be detected by immunoprecipitation of integrins from surface-labelled cells [25,34]. Whereas TM4 proteins were not directly identified here, Figure 2(B) reveals that several cellsurface proteins were detected in α $ immunoprecipitates, some of which had relative molecular masses corresponding to those reported previously [25,34] for members of this family (CD63, 45-55 kDa ; CD81, $ 22 kDa ; CD9, $ 23 kDa ; see asterisks in Figure 2B).…”
Section: Figure 2 Analysis Of Anti-α 3 Immunoprecipitates During Pc-3mentioning
confidence: 99%
“…It has been reported by others that members of the TM4 (tetraspan 4) family of cell-surface proteins can interact with some integrin α subunits, and that such interactions can be detected by immunoprecipitation of integrins from surface-labelled cells [25,34]. Whereas TM4 proteins were not directly identified here, Figure 2(B) reveals that several cellsurface proteins were detected in α $ immunoprecipitates, some of which had relative molecular masses corresponding to those reported previously [25,34] for members of this family (CD63, 45-55 kDa ; CD81, $ 22 kDa ; CD9, $ 23 kDa ; see asterisks in Figure 2B). However, the levels of none of these surface proteins found in α $ immune complexes changed significantly throughout time points in which levels of calreticulin were markedly altered (compare Figures 2B and 1B).…”
Section: Figure 2 Analysis Of Anti-α 3 Immunoprecipitates During Pc-3mentioning
confidence: 99%
See 1 more Smart Citation